Communicative and Collaborative Aspects in Indonesian BSE Evaluation Instruments - Safi'i, Imam; Wahdini, Lili (Journal of Education Research and Evaluation, 2021)
This article aims to describe the diversity of communicative and collaborative aspects contained in the evaluation instrument in Indonesian BSE. This study uses a qualitative approach by applying the principles of content analysis. The data sources in this study were 541 evaluation instruments spread over eight teaching materials, namely compiling procedural texts, studying explanatory texts, managing information in lectures, studying life in short stories, preparing proposals, designing scientific papers, assessing works through reviews, and performing plays. The results showed that overall the evaluation instruments relevant to various communicative competence indicators were 110 questions or 20.33% while the evaluation instruments relevant to various indicators of cooperative competence were 81 questions or 14.97%. This percentage shows that the communicative and collaborative competences in the evaluation instrument in Indonesian BSE have been developed quite well.